Detectability of Breast Tumor by a Hand-held Impulse-Radar Detector: Performance Evaluation and Pilot Clinical Study. Issue 1 (December 2017) - Song, Hang; Sasada, Shinsuke; Kadoya, Takayuki; Okada, Morihito; Arihiro, Koji; Xiao, Xia; Kikkawa, Takamaro
Abstract In this report, a hand-held impulse-radar breast cancer detector is presented and the detectability of malignant breast tumors is demonstrated in the clinical test at Hiroshima University Hospital, Hiroshima, Japan. The core functional parts of the detector consist of 65-nm technology complementary metal-oxide-semiconductor (CMOS) integrated circuits covering the ultrawideband width from 3.1 to 10.6 GHz, which enable the generation and transmission of Gaussian monocycle pulse (GMP) with the pulse width of 160 ps and single port eight throw (SP8T) switching matrices for controlling the combination of 4 × 4 cross-shaped dome antenna array. The detector is designed to be placed on the breast with the patient in the supine position. The detectability of malignant tumors is confirmed in excised breast tissues after total mastectomy surgery. The three-dimensional positions of the tumors in the imaging results are consistent with the results of histopathology analysis. The clinical tests are conducted by a clinical doctor for five patients at the hospital. The malignant tumors include invasive ductal carcinoma (IDC) and ductal carcinoma in situ (DCIS). The final confocal imaging results are consistent with those of Magnetic Resonance Imaging (MRI), demonstrating the feasibility of the hand-held impulse-radar detector for malignant breast tumors.